Inhibiting Properties of Morpholine as Corrosion Inhibitor for Mild Steel in 2N Sulphuric Acid and Phosphoric Acid Medium - K. Jayanthi; M. Sivaraju; K. Kannan (E-Journal of Chemistry)
The inhibition effect of morpholine on the corrosion of mild steel in 2N sulphuric acid and phosphoric acid has been studied by mass loss and polarization techniques between 302K and 333K. The inhibition efficiency increased with increase in concentration. The corrosion rate increased with increase in temperature and decreased with increase in concentration of inhibitor compared to blank. The adsorption of inhibitor on the mild steel surface has been found to obey Temkin's adsorption isotherm. Potentiostatic polarization results reveal that morpholine act as mixed type inhibitor. The values of activation energy (Ea), free energy of adsorption (∆Gads), enthalpy of adsorption (∆H), and entropy of adsorption (∆S) were also calculated.